Thermogenesis induced by amino acid administration prevents intraoperative hypothermia and reduces postoperative infectious complications after thoracoscopic esophagectomy. Issue 1 (21st December 2016) - Fujita, T.; Okada, N.; Kanamori, J.; Sato, T.; Mayanagi, S.; Torigoe, K.; Oshita, A.; Yamamoto, H.; Daiko, H.
SUMMARY: Minimally invasive thoracoscopic esophagectomy has potential advantages in minimizing the impairment of respiratory function and reducing surgical stress. However, thoracoscopic esophagectomy occasionally results in anesthesia-induced hypothermia, particularly in cases involving artificial pneumothorax with CO2 . Thermogenesis induced by amino acid administration has been reported during anesthesia. Here, we tested the efficacy of amino acid treatment for the prevention of hypothermia, and we investigated the potential of this treatment to reduce postoperative infectious complications after thoracoscopic esophagectomy. We conducted a randomized trial in patients with esophageal cancer who underwent thoracoscopic esophagectomy in the prone position in two groups and analyzed the incidences of hypothermia and surgical complications. One-hundred and thirty patients were randomized. Administration of amino acids resulted in a significant increase in core body temperature. In the saline ( n  = 60) and amino acid ( n  = 70) administration groups, 30% and 14.2% of patients, respectively, experienced infectious surgical complications ( P  = 0.029), and 21.6% and 22.8% of patients, respectively, experienced noninfectious surgical complications ( P  = 0.86). Univariate analysis revealed that blood loss and amino acid administration were significant factors for infectious surgical complications. Multivariate analysis revealed that amino acid administration was an independent factor reducing infectious surgical complications ( P  = 0.025, 95% confidence interval: 0.105–0.864). Administration of amino acids prevents hypothermia and reduces postoperative infectious complications after thoracoscopic esophagectomy.